2023
DOI: 10.1021/acs.jpcc.3c03893
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Elastic Constants of Tobermorite Enhanced with Reduced Graphene Oxide through Hydroxyl vs Epoxy Functionalization: A First-Principles Study

Mohammadreza Izadifar,
Jorge S. Dolado,
Peter Thissen
et al.

Abstract: Graphene-based materials are considered excellent candidates to implement cementitious nanocomposites due to their mechanical properties. This paper presents a comprehensive interface interaction that ends up with computing the elastic properties for four models of the C–S–H gel, taking tobermorite 14 Å as an example, with reduced graphene oxide (rGO) to form reinforced (tobermorite) cementitious nanocomposites within the density functional theory. We found that upon relaxing the model structures, the dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Fatigue damage in asphalt pavements, caused by continuous loading, primarily occurs at the asphalt binder-aggregate interface (adhesive failure) or within the asphalt binder itself (cohesive failure) [1,2]. Hence, the fatigue resistance of asphalt binders significantly impacts the ability of asphalt mixtures to withstand repetitive loading, garnering widespread attention from researchers [3][4][5][6][7][8][9]. There is still room for debate regarding whether traditional fatigue test methods and the resulting fatigue assessment models can accurately reflect the fatigue performance of asphalt binders under the influence of random loading [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue damage in asphalt pavements, caused by continuous loading, primarily occurs at the asphalt binder-aggregate interface (adhesive failure) or within the asphalt binder itself (cohesive failure) [1,2]. Hence, the fatigue resistance of asphalt binders significantly impacts the ability of asphalt mixtures to withstand repetitive loading, garnering widespread attention from researchers [3][4][5][6][7][8][9]. There is still room for debate regarding whether traditional fatigue test methods and the resulting fatigue assessment models can accurately reflect the fatigue performance of asphalt binders under the influence of random loading [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the advent of nanomaterials has introduced novel approaches to address these challenges and enhance the comprehensive performance of cement-based materials. Graphene oxide (GO) is a two-dimensional nanomaterial consisting of carbon, hydrogen, and oxygen elements, with a large specific surface area and edge effect. Due to its multiple functional enhancements, GO is widely utilized in various fields such as building materials , and batteries , to improve the performance and function of other materials. Furthermore, GO has been employed in cementitious nanocomposites, owing to its exceptional properties. Mohammadreza Izadifar et al utilized tobermorite with a length of 14 Å as a model to create enhanced tobermorite nanocomposite materials by incorporating reduced graphene oxide (rGO). Their research revealed a significant increase in the elastic constants of the composite material.…”
Section: Introductionmentioning
confidence: 99%
“…At the equilibrium condition, 66.50% of particles participated in the cluster formation. In addition, Izadifar et al [ 15 ] recently computed the enthalpy activation energy (Δ H ∗ ) at far-from-equilibrium conditions, which is based on the transition-state theory (TST) for the calculation of atomistic reaction rates for silicate tetrahedra dissolution in MK through the DFT computational approach [ 18 , 19 , 20 , 21 ]. Most published studies on geopolymer systems have focused on fly ash/blast furnace slag composite systems, and, in most cases, the examination has been limited to observing X-ray diffractograms and ultimate compressive strength, which are standard techniques in cement science.…”
Section: Introductionmentioning
confidence: 99%
“…The essential chemical and structural properties of geopolymers derived from metakaolinite, fly ash, and slag are investigated in terms of the impact of raw material selection on the properties of the geopolymer composites [ 3 ]. The use of geopolymer is a potential alternative to ordinary Portland cement, although the chemical and mechanical constitution of alkali activated mixes (AAMs) have not been understood and the pore structures of these materials have remained unexplored [ 10 , 18 , 19 ]. As a result, there is a great research opportunity to further investigate this topic.…”
Section: Introductionmentioning
confidence: 99%